Use of Dried and Fresh Aloe vera Barbadens as Feed Supplements and Their Effect on Broiler Performance - Silalahi, M; Hardjosworo, PS; Sinurat, AP; Purwadaria, T (ANIMAL PRODUCTION, 2009)
An experiment was conducted to evaluate the effect of supplementation effect of dried and fresh Aloe vera barbadens gels in broiler feed. 180 heads of one âday-old chickens were randomly allocated into 6 treatments, namely : (1) basal ration (BR) + 0,25 g dried gel of Aloe vera (DGAV)/kg ration, (2) BR + 0,50 g DGAV/kg ration, (3) BR + 1,00 g DGAV/kg ration, (4) BR + 25 g fresh gel of Aloe vera (FGAV)/kg ration, (5) BR + 50 g FGAV/kg ration, (6) BR + 100 g FGAV/kg ration. Each treatment was replicated 5 times and consisted of 6 chickens. Feed intake, weight gain, feed conversion ratio (FCR), percentage of carcass and abdominal fats, and mortality were examined. Data were analized by the complete randomized factorial design 2x3, except for data of FCR , which was descriptively analyzed. Result showed that feed intake and weight gain of broilers were not significantly affected by the physical form of A. vera gel. FCR based on live weight and the carcass of chickens feed by DGAV was better than chickens feed by FGAV. Dosses and physical form of A.Vera gel in ration did not significantly (P>0.05) affect the percentage of carcass and abdominal fat, and broilerâs Â mortality, for 5 weeks of observation. (Animal Production 11(1): 53-58 (2009)Key Words: aloe vera, feed, broiler